Structured Programming and Problem-Solving with PL/1 - Kieburtz Richard B (Prentice Hall, 1977)
An introductory text emphasizing the problem-solvingt approach to computing, progressing from the development of a systematic and disciplined approach to the discovery of algorithms. Preface, Glossary of Terms, What is Computing, Using Computational Variables, Programming the Computer to Make Decisions, Pepeating Computations, Telling the Computer about the Data, Getting Information in and out of a Computer, Computations Within Computations, Solving Hard Problems, Simulating the Real World, Numerical Computation, How Does the Computer Work, Index.